How Lean Six Sigma, Intellectual Capital and Good University Governance Influenced HEI Performance in Indonesia - Fauziana, Eva; Anggiani, Sarfilianty; Usman, Bahtiar (International Journal of Management and Business Applied, 2024)
Purpose – The purpose of this study is to analyze the influence of Lean Six Sigma mediated by Good University Governance to the Performance of 26 Muhammadiyah Aisyiyah private universities in Indonesia. Methodology/approach – The methodology using quantitative approach with Structural Equation Model (SEM) of the AMOS analysis. The study having samples of 245 respondents filling the online questionnaires from 26 private universities spread across all islands in Indonesia. Findings – Based on the results of the study, it is studied that both directly and indirectly Lean Six Sigma mediated by Good University Governance deeply positive and significant impacted to the performance of private universities in Indonesia. The practical implications of this study such as Six Sigma variables have a positive effect on the performance of 26 Muhammadiyah Aisyiyah private universities in Indonesia, although there are areas that need improvement, especially in the campus physical arrangement and infrastructure. Novelty/value – The value of this study such as giving contribution to the theoretical and its regulations implementation of Lean Six Sigma and Good University to support the university performance.